Structural analysis and molecular dynamics simulation studies of HIV-1 antisense protein predict its potential role in HIV replication and pathogenesis - Sathiyamani, Balakumaran; Daniel, Evangeline Ann; Ansar, Samdani; Esakialraj, Bennett Henzeler; Hassan, Sameer; Revanasiddappa, Prasanna D.; Keshavamurthy, Amrutha; Roy, Sujata; Vetrivel, Umashankar; Hanna, Luke Elizabeth (Frontiers in Microbiology, 2023)
The functional significance of the HIV-1 Antisense Protein (ASP) has been a paradox since its discovery. The expression of this protein in HIV-1 infected cells and its involvement in autophagy, transcriptional regulation and viral latency have sporadically been speculated in various studies. But the definite role of this protein in HIV-1 infection remains unclear. Deciphering the structure of HIV-1 ASP would throw light on its potential role in HIV lifecycle and host-virus interaction. Hence, using extensive molecular modelling and dynamics simulation for 200 ns, we predicted the plausible 3D-structure of ASP from two reference strains of HIV-1 namely, Indie-C1 (subtype-C) and NL4-3 (subtype-B) to predict the functional implication through structural domain analysis. In spite of sequence and structural differences between these subtypes, both structures were predicted to share common domains like Von Willebrand Factor Domain-A (VWFA), Integrin subunit alpha-X (ITGSX), ETV6-Transcriptional repressor, thereby reiterating the potential role of HIV-1 ASP in transcriptional repression and autophagy, as reported in earlier studies. Moreover, gromos based cluster analysis of the centroid structures reassured the accuracy of the prediction. This is the first study to elucidate a highly plausible structure for HIV-1 ASP which could serve as a feeder for further experimental validation studies.